PEMBUATAN KERIPIK DARI LIMBAH DEBOG PISANG DI DESA PONDOK BUNGUR KECAMATAN RAWANG PANCA ARGA - Rosnaida Rosnaida; Abdul Rahman; Henky Japina (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service activity aims to enhance the skills and entrepreneurial spirit of local residents, particularly housewives in Pondok Bungur Village, Rawang Panca Arga Subdistrict, Asahan Regency, through training on utilizing banana pseudo-stem (debog) waste into value-added chip products. The background of this program lies in the underutilization of household organic waste, which poses both environmental and economic challenges. The implementation method includes socialization, material delivery, hands-on training, and participatory evaluation using Focus Group Discussions (FGDs). The evaluation process applied two relevant approaches: participatory and reflective evaluation to gather feedback from participants, and problem-based evaluation to identify and solve technical barriers during the training. The results showed a significant improvement in participants' understanding, practical skills, and motivation to process banana pseudo-stem waste into economically valuable products. Moreover, some participants demonstrated an initiative to start small-scale businesses based on local resources. This activity proves that training on organic waste utilization can be a sustainable strategy for family economic empowerment.